Nate the Great and the sticky case - Sharmat, Marjorie Weinman; Simont, Marc. (New York : Coward, McCann & Geoghegan, 1978)
Nate the Great and his dog Sludge try to track down Claude's missing Stegosaurus stamp.
Booklist
2.0
K-3
Keywords: Mystery and detective stories; Dinosaurs -- Fiction; Mystery and detective stories; Dinosaurs -- Fiction